Analysis of characteristics of intracranial cavernous angioma and bleeding factors in middle-aged and elderly patients - Xiu, Chao; Ni, Donghe; Zhao, Jincui; Yu, Yang (Frontiers in Neurology, 2023)
Objective Intracranial cavernous angioma (ICA) is a cerebrovascular malformation. It causes local neurological dysfunction, epilepsy, intracranial hemorrhage (ICH) and other symptoms, seriously affecting the safety of patients. This study analyzed middle-aged and elderly patients with ICA in our hospital, summarized the characteristics of the disease and investigated the related factors of ICH. Methods We conducted a retrospective analysis of 120 middle-aged and elderly patients who were diagnosed with ICA by magnetic resonance imaging in our hospital from March 2018 to September 2021. The cases were assigned to either a bleeding group (i.e., the experimental group) or a non-bleeding group (i.e., the control group). The characteristics of the disease, including gender, age, number of lesions, form and symptoms of onset, distribution of lesions, blood supply vessels in the lesion area, size of the lesion and presence of bleeding, were summarized and analyzed. The relationship between these factors and ICH was investigated, and the data were analyzed using SPSS 25.0 software. Results There were 56 cases in the experimental group and 64 cases in the control group. A univariate analysis showed that gender, age, body mass index, blood lipids, number of lesions, course of the disease, onset of symptoms and disease characteristics were not associated with ICH in the middle-aged and elderly patients with ICA (P > 0.05). The maximum diameter, volume, location and blood supply area of the lesions were related to ICA complicated with ICH (P < 0.05). A multivariate unconditional logistic regression analysis revealed that the maximum diameter, volume, location and blood supply area of the lesions were independent risk factors for ICH in the middle-aged and elderly patients with ICA. The odds ratio (OR) of the maximum diameter of the lesion was 4.410, the OR of the lesion volume was 7.316, the OR of the lesion site was 7.470, and the OR of the blood supply area was 1.6588. Conclusion Intracranial cavernous angioma lesions in middle-aged and elderly patients occur mainly in the supratentorial area, with a small part located in the infratentorial area. The main form of the disease is chronic recurrence. The occurrence of bleeding is related to the size, location and blood supply of the lesion.